Water Resources Users Associations in the Mara Basin, Kenya: Pitfalls and Opportunities for Community Based Natural Resources Management - Richards, Nathalie; Syallow, Dorothy (Frontiers in Environmental Science, 2018)
Water Resources Users Associations (WRUAs) in the Mara Basin, Kenya, are community-based natural resources management institutions set-up following the Integrated Water Resources Management framework. They are the most local participatory governance structure currently in place managing the tributaries of the Mara river. WRUAs are the link between environmental services from the river and livelihoods of local communities. Opportunities and pitfalls for the undertaking of their roles are assessed through the analysis of four WRUAs. Recognition of local knowledge, procedural considerations in the setting-up and carrying out of activities, as well as distributional aspects of the WRUA undertakings are evaluated in the paper. The authors argue that typical issues identified in critical community management literature appear in this case study: elite capture, dependency on donor support, lack of meaningful participation, and difficulties for scaling up initiatives. However, WRUAs have positively impacted environmental services in a localized and indirect manner, opening opportunities in terms of awareness, scaling water conservation initiatives, and conflict resolution. Future development of WRUAs can improve environmental flows particularly if a targeted follow-up is maintained by encouraging leadership and monitoring the relationship between donors, elites, and marginalized community members.